PROFESSIONALISM AMONG MEDICAL STUDENTS AT TWO PUBLIC SECTOR UNIVERSITIES "” A COMPARATIVE STUDY - Bhutto, Shahzadi Nisar; Asif, Mariam; Jawaid, Masood (Journal of Postgraduate Medical Institute, 2015)
Objective: To determine the level of professionalism among undergraduatemedical students at two public sector medical colleges of Karachi, Pakistan. Methodology: This cross sectional study was conducted from August to November2013 in two medical Universities of Karachi [Dow University of HealthSciences (DUHS) and Jinnah Sindh Medical University (JSMU)]. The validatedProfessionalism Instrument used in survey forms measured 6 tenets of professionalism(i.e. altruism, accountability, excellence, duty, honor and integrity,respect for others) and exhibited satisfactory reliability measures. The surveyforms were pretested and a pilot data collection was performed to check theresponse and make sure the ease of participants. The study sample comprisedof first through final year students of each medical school. The students wereasked to fill a structured survey form after verbal information and consent. Only those students were included who were enrolled in the respective medicalschool and present on the day of survey. The data was analyzed using SPSSversion 16 and Independent sample T-test was applied to compare meanscores of each tenet between the groups. Results: Among 494 respondents (302 from DUHS, 192 from JSMU) the meanscore of all six tenets of professionalism turned out to 11.43. There was aslight variation found in each tenet score in first and final year students, mostmarked being in "˜honor and integrity' (Pre-clinical=11.91, Clinical=11.38). Altruism(11.44), honor and integrity (11.91) were higher in pre-clinical groupwhereas students from third to final year were more devoted (11.21), accountable(11.48), and excellent (11.73). Conclusion: The current level of professionalism among medical students issub-optimal. To achieve an optimum state, professionalism should be includedformally in undergraduate medical curriculum.